Knowledge, attitude and practices (KAP) of smallholder livestock farmers around heartwater diseases : a case of Bushbuckridge, Mpumalanga Province, South Africa - Aphane, Tidimalo Mokgoro (My University, 2024)
Heartwater, stemming from Ehrlichia ruminantium and transmitted by Amblyomma ticks, is a significant infectious threat to ruminants, imposing constraints on animal production. The susceptibility of smallholder livestock farmers to disease outbreaks, particularly heartwater, is heightened by challenges in implementing effective animal health practices. There is relatively little insight and understanding of the Tick-borne disease (TBD), despite it being regarded as one of the deadliest diseases for livestock in places where it is endemic. The research aimed to assess the knowledge, attitude and practices (KAP) of smallholder livestock farmers towards heartwater disease in Bushbuckridge Local Municipality in Mpumalanga Province, South Africa. Specifically, this study profiled the smallholder livestock farmers, analysed their KAP towards heartwater disease and finally, analysed factors influencing their KAP in the study area. This study sampled 180 smallholder livestock farmers through the multistage sampling technique. Primary cross-sectional data, which was collected using structured questionnaires were used in this study. Descriptive statistics, KAP survey framework, which used Likert scale and the Multinomial Logistic Regression (MLR) model were used to address the study objectives. The key findings revealed a majority of male farmers with an average age of 59, often possessing only primary education. A general lack of knowledge about heartwater disease influenced farmers' attitudes and practices. The MLR model identified eight influential variables, including gender, income sources, access to animal handling facilities, and annual expenditure, impacting the KAP of smallholder livestock farmers. The study recommended prioritizing government efforts to disseminate information on heartwater, addressing farmers' knowledge gaps. Moreover, subsidies for expensive animal health medication and vaccines were proposed to alleviate financial challenges faced by the majority of smallholder farmers.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Heartwater disease; Knowledge; Attitude and practices; Multinomial Logistic Regression; Smallholder livestock farmers; Heartwater; Logistic regression analysis; Livestock -- Diseases; Farmers -- South Africa -- Mpumalanga